Integration of medication for opioid use disorder training into graduate nursing education. Issue 5 (26th May 2022) - Barcelona, Veronica; Wischik, Dora L.; Marshall, Ami; Tetrault, Jeanette M.
Abstract: The COVID‐19 pandemic has further limited access to treatment for opioid use disorder (OUD). Advanced practice registered nurses can reduce opioid related complications and overdose by obtaining a Drug Enforcement Administration (DEA) regulated X‐waiver that allows for prescription of medications for OUD (MOUD) in general medical settings. Graduate nursing education, where advanced practice nurse practitioner (NP) students are educated, has not incorporated this content into standard curricula. We describe an innovative approach to incorporate DEA X‐waiver training in a required community health NP in partnership with addiction medicine clinicians. Advanced practice NP students ( N  = 114) either completed fully online or hybrid (virtual didactic and online) X‐waiver training on MOUD. We describe how an interprofessional partnership to incorporate MOUD education into graduate nursing curricula is a feasible method for training students to treat OUD in the context of the pandemic. This approach is responsive to the crucial need for more health care providers to address the opioid overdose crisis.